Sounding the Unheard River: Reflections on an Ecological Sound Art Praxis as a Response to Ecosystem Distress. Issue 1 (May 2019) - Morgan, Trish
Abstract : This article reflects on a body of academic and practice-based work in the contexts of praxis. It asserts that in the face of systemic issues pertaining to ecosystem crisis, multidisciplinary approaches are required, which also enable the agency of the researcher to continue their work in challenging circumstances. In reflecting on the work conducted, the article aims to offer an insight into multiple ways in which knowledge about ecosystem distress can be communicated to multiple audiences. Furthermore, in providing a reflexive account of an ecological sound art project titled The Miracle of the One Thing, the article aims to shed light on the role of practice-based approaches in communicating ecosystem distress. It implicitly offers an alternative to the 'ocularcentrism' of the visual turn. It questions the assumption that communication about ecosystem crisis is necessarily visual or written, and places the role of sonic practices to the fore.